Monte Carlo simulation of free radical production under keV photon irradiation of gold nanoparticle aqueous solution. Part I: Global primary chemical boost. (July 2020) - Poignant, Floriane; Charfi, Hela; Chan, Chen-Hui; Dumont, Elise; Loffreda, David; Testa, Étienne; Gervais, Benoit; Beuve, Michaël
Abstract: The use of gold nanoparticles to enhance radiation therapy efficiency has been thoroughly investigated over the past two decades. While theoretical studies have mostly focused on physical mechanisms and dose enhancement, studies of free radical production are scarce. In this work, we investigated the primary yield of free radicals ( O H and H 2 O 2 ) induced by 20–90 keV monoenergetic photons, for small GNPs concentrations. Our study is based on a Monte Carlo approach which enables electron transport down to low energy, both in water and in gold. We obtained, for a gold concentration of 1 mg ⋅ mL − 1, an average chemical enhancement varying from 6 to 14%, depending mostly on the photon energy and, to a lesser extent, on the chemical species and size of the GNP. This enhancement is strongly correlated to the dose deposition enhancement, although not strictly proportional. While supporting the hypothesis that therapeutic efficiency of GNPs may not simply be explained by an overproduction of free radicals in the early stage, our simulation provides inputs for further macroscopic simulations, including cumulative track effects and potentially GNP chemical reactivity. Highlights: We calculate radiolitic yields of free radicals for 20–90 keV photon irradiation of gold nanoparticle water solution. 1 mg/mL of GNPs increases radical production from 6 to 14%. Radical production enhancement is similar to the dose enhancement.